Serotonin innervation of the subthalamic nucleus in parkinsonian monkeys - C.V.L. Delmas; J. Munro; M. Bérard; T. Di Paolo; M. Morissette; M.E. Tremblay; A. Parent; M. Parent (Neurobiology of Disease)
The subthalamic nucleus (STN), the main driving force of the basal ganglia, is innervated by brainstem serotonin (5-HT) neurons with highly plastic axonal arborization. A pathologically-induced rearrangement of the ascending 5-HT projections could contribute to the disrupted firing pattern of STN neurons observed in Parkinson's disease (PD). This light and electron microscope study was designed to characterize the neuroadaptive changes of 5-HT inputs to the different functional territories of the STN in four cynomolgus monkeys (Macaca fascicularis) rendered parkinsonian by systemic injections of 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) and four control animals. Using an unbiased stereological approach, we report a significant decrease of the density of 5-HT axon varicosities immunolabeled for the 5-HT membrane transporter (SERT), across all STN functional territories of MPTP-treated monkeys. In MPTP-treated animals, the SERT+ axon varicosities are larger than in control monkeys. In both experimental conditions they are only partially synaptic. A preserved length of 5-HT axons in the STN along with a conserved number of 5-HT neurons in the dorsal raphe nucleus is observed. Overall, our results indicate that, in parkinsonian monkeys, the 5-HT axons projecting to the STN are preserved but endowed with significantly less axon varicosities. Such neuroadaptive change could lead to a lower ambient level of 5-HT in this basal ganglia component, representing a compensatory mechanism designed to cope with the hyperexcitability of STN neurons that is known to occur in PD.